PERTANGGUNGJAWABAN PIDANA BAGI PELAKU EIGENRICHTING (MAIN HAKIM SENDIRI) YANG MENGAKIBATKAN KORBAN JIWA MENURUT KUHP (Studi Putusan Nomor 8/PID. B/2018/PN. BKS) - Siregar, Astopan; Marlina, Marlina; Affan, Ibnu (Jurnal Ilmiah METADATA, 2021)
Violence is indeed a phenomenon that is often encountered in Indonesian society lately. In fact, the existing law in Indonesia has not been able to provide strict punishments for perpetrators of vigilantism (eigenrichting). The formulation of the problem in this thesis is how to regulate criminal offenses in the form of vigilante actions according to the Criminal Code, how to qualify for vigilante offenses (eigenrichting) that result in fatalities in criminal law, what is the basis for judges' considerations in making decisions against perpetrators of vigilante action. (eigenrichting) in Decision Number 8/PID.B/2018/PN. Bks. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the regulation of criminal offenses in the form of taking vigilante action according to the Criminal Code is regulated in Article 170, Article 351, Article 406, Article 338 and in the decision of the act as regulated and threatened with punishment in the decision Number 8/Pid. B/2018/PN. Bks perpetrators of acts of vigilantism were charged with Article 170 paragraphs (1) and (2) in conjunction with Article 55 paragraph (1) 1st of the Criminal Code. The qualification for the offense of vigilante action (eigenrichting) that results in fatalities in criminal law is that the defendant has fulfilled all the elements of the indictment in Article 170 of the Criminal Code so that the panel of judges sentenced the defendant to imprisonment for 8 (eight) years. The basis for the judge's consideration in making a decision against the perpetrator of the vigilante act (eigenrichting) is in Decision Number 8/PID.B/2018/PN. Bks is that during the trial process there was no forgiving reason or justification that could erase the criminal and unlawful nature of the defendant.